High collocation of sand lance and protected top predators: Implications for conservation and management. Issue 2 (6th October 2020) - Silva, Tammy L.; Wiley, David N.; Thompson, Michael A.; Hong, Peter; Kaufman, Les; Suca, Justin J.; Llopiz, Joel K.; Baumann, Hannes; Fay, Gavin
Abstract: Spatial relationships between predators and prey provide critical information for understanding and predicting climate‐induced shifts in ecosystem dynamics and mitigating human impacts. We used Stellwagen Bank National Marine Sanctuary as a case study to investigate spatial overlap among sand lance ( Ammodytes dubius ), a key forage fish species, and two protected predators: humpback whales ( Megaptera novaeangliae ) and great shearwaters ( Ardenna gravis ). We conducted 6 years (2013–2018) of standardized surveys and quantified spatial overlap using the global index of collocation. Results showed strong, consistent collocation among species across seasons and years, suggesting that humpback whales and great shearwater distributions are tightly linked to sand lance. We propose that identifying sand lance habitats may indicate areas where humpbacks and shearwaters aggregate and are particularly vulnerable to human activities. Understanding how sand lance influence predator distributions can inform species protection and sanctuary management under present and future scenarios.